A Multicenter Study of IMRT Dosimetry Audit Testing Using C-shape Phantom - Dwinesti, B.; Ryangga, D.; Dimitri, F.; Handika, A. D.; Fadli, M.; Putranto, A. M. Y.; Suharsono, S; Pawiro, S. A. (National Research and Innovation Agency, 2025)
Intensity Modulation Radiation Therapy (IMRT) is a complex radiotherapy technique, so independent verification or dosimetry audits must be performed to ensure that accurate dosing is delivered to patients. This study conducted a multicenter audit using a dosimetry audit method developed from the IAEA dosimetry audit for IMRT/VMAT. The phantom in this study is made of acrylic material with two insert structures: planning target volume (PTV) and organ at risk (OAR). Phantom was scanned with a CT simulator at each hospital, and dose distribution was simulated with a PTV prescription dose of 4 Gy/2 fraction (D95 % = 95 %, D2 % < 107 %, and Dmax < 110 %) and a maximum OAR dose of 2.8 Gy. Dose evaluation in this study used TLD-rod for point dose and Gafchromic Film EBT3 for 2D dose distribution. Gamma evaluation was performed for film dose distribution with 3 %/3 mm and 3 %/2 mm criteria. The IMRT dosimetry audit using a C-shape phantom was tested in seven linacs (dynamic and static MLC) from six centers in Jakarta. The TLD results for PTV and OAR point dose show that all 14 IMRT plans meet deviation tolerance within ± 5 %. The film EBT3 evaluation identified that almost all plans pass the minimum 95 % gamma passing rate for 3 %/3 mm criteria and the minimum of 90 % for 3 %/2 mm. Three plans from three centers were also compared to the Gayatri (2022) study data from the same centers. Both results showed that all plans pass the action level ≥ 90 % for both 3 %/2 mm and 3 %/3 mm. Our audit dosimetry study approach employs a small and compact C-shaped phantom and dosimetry, facilitating easier distribution for remote audits. This study could serve as a starting point for remote audits leading to broader multicenter research in Indonesia.